Intercellular communication between artificial cells by allosteric amplification of a molecular signal - Bastiaan C. Buddingh’ (Nature Portfolio, 2020)
The principles of intercellular communication in multicellular organisms can be explored using artificial cells. Here, the authors report on giant vesicles which can recognize diffused chemical signals and amplify the signal by synthetic enzymatic cascades to allow signal propagation over long distances.